Activation of the yeast Retrograde Response pathway by adaptive laboratory evolution with S-(2-aminoethyl)-L-cysteine reduces ethanol and increases glycerol during winemaking - Víctor Garrigós; Cecilia Picazo; Emilia Matallana; Agustín Aranda (Microbial Cell Factories, 2024)
Abstract Background Global warming causes an increase in the levels of sugars in grapes and hence in ethanol after wine fermentation. Therefore, alcohol reduction is a major target in modern oenology. Deletion of the MKS1 gene, a negative regulator of the Retrograde Response pathway, in Saccharomyces cerevisiae was reported to increase glycerol and reduce ethanol and acetic acid in wine. This study aimed to obtain mutants with a phenotype similar to that of the MKS1 deletion strain by subjecting commercial S. cerevisiae wine strains to an adaptive laboratory evolution (ALE) experiment with the lysine toxic analogue S-(2-aminoethyl)-L-cysteine (AEC). Results In laboratory-scale wine fermentation, isolated AEC-resistant mutants overproduced glycerol and reduced acetic acid. In some cases, ethanol was also reduced. Whole-genome sequencing revealed point mutations in the Retrograde Response activator Rtg2 and in the homocitrate synthases Lys20 and Lys21. However, only mutations in Rtg2 were responsible for the overactivation of the Retrograde Response pathway and ethanol reduction during vinification. Finally, wine fermentation was scaled up in an experimental cellar for one evolved mutant to confirm laboratory-scale results, and any potential negative sensory impact was ruled out. Conclusions Overall, we have shown that hyperactivation of the Retrograde Response pathway by ALE with AEC is a valid approach for generating ready-to-use mutants with a desirable phenotype in winemaking.